Economic value assessment of edible plants in Muang District, Kalasin Province, Thailand - NATTHAKIT PHATLAMPHU; SURAPON SAENSOUK; PIYAPORN SAENSOUK; AUEMPORN JUNSONGDUANG; AHMAD DWI SETYAWAN (Society for Indonesian Biodiversity, 2023)
Abstract. Phatlamphu N, Saensouk S, Saensouk P, Junsongduang A, Setyawan AD. 2023. Economic value assessment of edible plants in Muang District, Kalasin Province, Thailand. Biodiversitas 24: 3960-3967. Edible plants have been traded as economic plants for food consumption, and their supply can be used at the industry level. However, modern agriculture might be disrupting a local plant value that the indigenous people use as their food in daily life. Therefore, this study aimed to assess the economic value of edible plants in Muang District, Kalasin Province, based on their market value and trading volume in a year. Data were collected through a pricing survey in the municipal and local markets from March 2019 to February 2021. The value was applied using the formula of the economic Value of Edible Plants (EVEP) that focus on the local scale of economy to explore the relationships between edible plant traders and consumers in the study area. There were 78 edible plant species that belonged to 67 genera and 41 families. The highest value is Oryza sativa L. (rice) which gains income averaging 684,000 THB annually/trader, followed by Coriandrum sativum L. (coriander) and Alpinia galanga (L.) Willd. (galangal) with averaging values of 216,000 and 187,200 THB annually/trader, respectively. When we identified the edible plants into two groups based on their sources, including the economic plants and the local plants, they were found 40 species of economic plants (51%) and 38 species of local plants (49%). In addition, we found that 43 species of edible plants were traded throughout the year (12 months), including 14 species of local plants (32.6%) and 29 species of economic plants (67.4%). That shows the risk trend of local plant consumption loss is due to the growth of economic plants.